1995
DOI: 10.1016/0896-6273(95)90175-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in visual sensitivity by changes in local context: Parallel studies in human observers and in V1 of alert monkeys

Abstract: To explore the role of primary visual cortex in contour integration, we measured the contextual sensitivity of human contrast thresholds and of superficial layer complex cells in monkey V1. An observer's contrast detection was 40% improved by a second suprathreshold bar; the effect was decreased as the two bars were separated along their axis of orientation, were displaced from colinearity, and had their relative orientation changed. Recordings from V1 showed that 42% of complex cells demonstrated facilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
633
8
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 847 publications
(687 citation statements)
references
References 43 publications
43
633
8
3
Order By: Relevance
“…For instance studies have shown that when a line is presented with two flanking lines its enhancement is greater than if one of the flankers is in the shape of a T (Kapadia et al 1995). Such a result might be predicted by our model since the flanking T would then be promoted to have a higher saliency value Fig.…”
Section: Sensitivity To Junctionsmentioning
confidence: 54%
See 1 more Smart Citation
“…For instance studies have shown that when a line is presented with two flanking lines its enhancement is greater than if one of the flankers is in the shape of a T (Kapadia et al 1995). Such a result might be predicted by our model since the flanking T would then be promoted to have a higher saliency value Fig.…”
Section: Sensitivity To Junctionsmentioning
confidence: 54%
“…As has been discussed, contour integration behavior can be seen in cases where only a few Gabor or other directionally specific element, such as a line segment, flank one element (Polat and Sagi 1993a,b;Kapadia et al 1995;Gilbert et al 1996;Kapadia et al 2000;Freeman et al 2003). We attempted to replicate work by Polat and Sagi (1993a,b) showing that a Gabor element when flanked by one collinear Gabor on either side can be enhanced from this arrangement.…”
Section: Local Element Enhancementmentioning
confidence: 99%
“…Activating an expectation of 'yellow balls' enables more rapid detection of a yellow ball, and with a more energetic neural response, than if you were not looking for it. Neural correlates of such excitatory priming and gain control have been reported by several laboratories [46][47][48][49][50][51][52] . Sensory and cognitive topdown expectations hereby lead to excitatory matching with confirmatory bottom-up data.…”
Section: Complementary Expectation Learning and Matching During 'Whatmentioning
confidence: 81%
“…It has been proposed (Field et al, 1993;Kovacs, 1996;Polat, 1999) that this spatial linking is mediated by long-range horizontal connections in the primate striate cortex (V1) that link distant neurons with similar orientation properties and form nonclassical receptive fields (Mitchison & Crick, 1982;Rockland & Lund, 1983;Ts'o & Gilbert, 1988;Malach et al, 1993;Kapadia et al, 1995;Zipser et al, 1996;Sincich & Blasdel, 2001). However, it is not yet known to what extent these long-range connections are limiting contour integration, and how their facilitatory effect is modulated by chromaticity, spatial frequency, or other visual attributes.…”
Section: Introductionmentioning
confidence: 99%